Siblings with Xeroderma Pigmentosum: A Case Report - Begum, Tamanna; Mannan, Abdul; Khan, Md Shafique Ahmmed; Hossain, Shahadat; Ali, Ahammed (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v30i1.6182 Bangladesh J Child Health 2006; VOL 30 (1/2/3): 32-35